2009
DOI: 10.1038/nature07670
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive polymorphism survey elucidates population structure of Saccharomyces cerevisiae

Abstract: Comprehensive identification of polymorphisms among individuals within a species is essential both for studying the genetic basis of phenotypic differences and for elucidating the evolutionary history of the species. Large-scale polymorphism surveys have recently been reported for human 1 , mouse 2 , and Arabidopsis thaliana 3 . Here we report a nucleotide-level survey of genome variation in a diverse collection of 63 S. cerevisiae strains sampled from different ecological niches (beer, bread, vineyards, immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

33
491
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 414 publications
(527 citation statements)
references
References 29 publications
33
491
2
1
Order By: Relevance
“…Structural variation, although abundant, was limited to the end sections of chromosomes. A similar pattern has been previously observed in microarray-based surveys of genome variation among different S. cerevisiae strains (Winzeler et al 2003;Carreto et al 2008;Schacherer et al 2009), which found that most polymorphisms, including SNPs and CNVs, were more common within 25 kb of the telomeres. In these studies, however, the full extent of the structural variation in these regions could not be revealed because the microarrays used were based on the S288c genome, and regions of high sequence divergence or sequences that were absent in the reference strain could not be examined.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Structural variation, although abundant, was limited to the end sections of chromosomes. A similar pattern has been previously observed in microarray-based surveys of genome variation among different S. cerevisiae strains (Winzeler et al 2003;Carreto et al 2008;Schacherer et al 2009), which found that most polymorphisms, including SNPs and CNVs, were more common within 25 kb of the telomeres. In these studies, however, the full extent of the structural variation in these regions could not be revealed because the microarrays used were based on the S288c genome, and regions of high sequence divergence or sequences that were absent in the reference strain could not be examined.…”
Section: Discussionsupporting
confidence: 60%
“…Microarray-based whole-genome hybridization studies of wild, industrial, and laboratory S. cerevisiae strains (Winzeler et al 2003;Carreto et al 2008;Faddah et al 2009;Schacherer et al 2009) have uncovered a recurrent pattern of copy number variation (CNV) near the ends of chromosomes, suggesting a role for repetitive DNA sequences in structural genome diversification. Despite these valuable insights, two central questions regarding the role of chromosomal rearrangements in genome evolution in S. cerevisiae remain unanswered: First, it is still unclear how these rearrangements contribute to long-term fitness in natural environments; and second, it is not known if they are compatible with the formation of viable meiotic spores that would allow their sexual dissemination between natural S. cerevisiae populations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These conditions, as well as unwitting selection by man for optimal winemaking traits (fermentation performance, alcohol tolerance, and good flavor production) have generated hundred of strains that are currently used in the wine industry. As a result, wine yeast isolates belong to a well-defined lineage (2)(3)(4)(5)(6).…”
mentioning
confidence: 99%
“…Numerous methods have been used to assay genomic variation in yeast and determine relationships between strains, and also used to infer strain origins and history (e.g., Schuller et al 2004;Legras et al 2005). Such studies include comparative analyses of microsatellites (Legras et al 2007;Franco-Duarte et al 2009;Muller and McCusker 2009b;Richards et al 2009), mini-and megasatellites (Richard and Dujon 2006;Rolland et al 2010), copy number variation using aCGH (PĂ©rez-OrtĂ­n et al 2002;Infante et al 2003;Winzeler et al 2003;Dunn et al 2005;Carreto et al 2008;Kvitek et al 2008), and polymorphisms detected by tiling arrays (Schacherer et al 2009), as well as the use of multispecies 131-gene taxonomic microarrays (Muller and McCusker 2009a) and Multi Locus Sequence Typing (MLST) (Fay and Benavides 2005a,b;Ayoub et al 2006;Vigentini et al 2009). These studies have mostly shown that yeasts used for a particular industrial use appear to be more closely related, but that geographical migrations, as well as genetic drift, have influenced diversity among S. cerevisiae populations (Legras et al 2007).…”
mentioning
confidence: 99%